Technological solutions for air pollution control to mitigate climate change: an approach to facilitate global transition toward blue sky and net-zero emission - Kurniawan T.A.; Khan S.; Mohyuddin A.; Haider A.; Lei T.M.T.; Othman M.H.D.; Goh H.H.; Zhang D.; Anouzla A.; Aziz F.; Mahmoud M.; Ali I.; et al. (Springer Science and Business Media Deutschland GmbH, 2025)
The convergence of air pollution control and climate change mitigation is critical in the pursuit of sustainable development. Therefore, technological innovations are pivotal in addressing the dual challenges of air pollution and global warming. This work presents an overview of technological solutions aimed at reducing air pollution and mitigating GHG emissions. While evaluating their technological strengths and limitations in real applications, this work offers a framework to promote a transition toward blue skies and net-zero emissions. This work also identifies the main sources and negative impacts of air pollution on public health and the environment. A literature overview of published articles from 1976 to 2024 showed that integrating emission reduction technologies are vital in real-word applications. More than 98% of the SO2 in the flue gas can be removed using cutting-edge desulfurization technology. SO2 is eliminated from the environment either unaltered or as sulfuric acid and sulfates. Meanwhile, thermal incinerators boast an impressive efficiency, capable of eliminating 99% of gaseous pollutants. Although existing pollution control technologies are promising to mitigate climate change, they still require further research, development, demonstration, and deployment to overcome barriers and achieve their potential. By examining the effectiveness of control technologies and proposing adaptable strategies, this work highlights the potential of integrating air quality improvement efforts with climate actions. Not only this addresses the global need for cleaner air, but also contributes to the overarching goal of climate stabilization. ? The Author(s), under exclusive licence to the Institute of Chemistry, Slovak Academy of Sciences 2024.